What Are the Incentives for Medicare Prescription Drug Plans to Consider Long-Term Outcomes and Cost? - Hung, Anna; Perfetto, Eleanor M. (Journal of managed care & specialty pharmacy, 2016)
Medicare Prescription Drug Plans (PDPs) do not have incentives to consider long-term outcomes and costs associated with both medical and pharmacy benefits (LTOCMP) when making formulary decisions. To identify existing quality measures, payment models, and public reporting tools for PDPs that are related to formulary decision making and that could be used as potential incentives for PDPs to consider LTOCMP. PubMed, Google, and quality measure databases, as well as Center for Medicare and Medicaid Innovation and Centers for Medicare & Medicaid Services (CMS) websites, were searched for appropriate quality measures, payment models, and public reporting tools. Few quality measures and other mechanisms exist that are related to formulary decision making and have the potential to be incentives for PDPs to consider LTOCMP. Only 3 such tools were identified: (1) Medicare Part D star ratings quality measures in use by CMS, (2) the Medicare Plan Finder website, and (3) URAC PBM Accreditation standards and measures. Furthermore, the majority of the quality initiatives identified were only indirectly related to motivating PDPs to consider LTOCMP. Efforts are needed to develop mechanisms to align PDP incentives with LTOCMP. No outside funding supported this research/study. Hung reports part-time employment by CVS Health and Blue Cross Blue Shield Association, as well as past paid internships with Biotechnology Industry Organization and AMCP Foundation/Allergan. Perfetto reports advisory board, consultancy, and lecture fees from Pfizer, Otsuka, Sanofi, National Pharmaceutical Council, and AMCP Foundation, as well as employment by the National Health Council and Journal of Managed Care & Specialty Pharmacy. Both authors contributed to study concept and design, data interpretation, and manuscript revision. Hung collected the data and prepared the manuscript.